Coping with Crises : Why and How to Protect Employment and Earnings - Paci, Pierella (2012)
Events of the past two years are a reminder that crises are a recurring phenomenon with deep and often protracted impacts on labor markets. This paper examines the challenges inherent in crafting policy responses, with particular attention to developing countries. It focuses on the potential tradeoffs between offsetting adverse short-term impacts and preserving incentives for economic recovery and future growth, and between protecting the most vulnerable and compensating those most immediately impacted. It also highlights how policymakers room for maneuver is constrained in crisis times by deteriorating fiscal space, limited institutional capacity, and mounting political pressures. Based on empirical evidence from previous crises, the paper asserts that taking a myopic and reactive approach may be costly and counterproductive. Instead, it advocates a more comprehensive approach, designed to build institutions - such as automatic stabilizers and safety nets - that can deliver a coordinated and coherent policy package. This approach will make crises catalysts for institutional changes and long-run growth.